The effect on tensile and surface morphological properties of oil palm empty fruit bunch fibre through hot water treatment - Abu Bakar, H; Ismail, L H; Nik Soh, N M Z; Samsudin, E M; Astimar, A A (2023)
The utilisation of Oil Palm Empty Fruit Bunch (EFB) fibre, a significant crop in Malaysia, is a viable option for incorporation into cement-based products due to the substantial amount of waste it generates. Nevertheless, the presence of extractives has a significant impact on the performance of EFB fibre and leads to an inherent incompatibility between EFB fibre and cement. Hence, the purpose of this study was to investigate the impact of varied temperatures and soaking durations on the physical and mechanical properties of EFB fibre as a reinforcement material. This research aimed to contribute new insights into the performance of these qualities under varying conditions. The result from the tensile strength shows that the EFB fibre increased dramatically with temperature at all soaking times. Nevertheless, extended periods of soaking have been found to have a detrimental effect on the tensile strength of fibres due to the process of deterioration. This leads to a weakening or damage to the fibres. Thus, the surface morphology observation proved that as temperature increased, the number of silica bodies removed from the fibre surface increased (800 C, 900 C and 1000 C) at all soaking hours. However, starting at 700 C (3 hour soaking time), the circular craters on the surface and the lignin layer start to damage. Therefore, these findings exhibit considerable potential for future investigation in substantiating the viability of employing EFB fibres as reinforcement agents in composite materials